PLCs programming common functions - RIMEDIA Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The PLCs: Programming Common Functions training program, or unit, is designed to familiarize trainees with the basics of programming common functions for a programmable logic controller. After completing this program, the trainees should be able to identify common non-I/O PLC instructions and explain how they are used.
Keywords: Computer programming -- Specifications; Programmable logic devices -- Design and construction; Programming languages (Electronic computers)